2019
DOI: 10.3390/w11112289
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Method Tracking of Monsoon Floods Using Sentinel-1 Imagery

Abstract: Floods cause great losses in terms of human life and damages to settlements. Since the exposure is a proxy of the risk, it is essential to track flood evolution. The increasing availability of Synthetic Aperture Radar (SAR) imagery extends flood tracking capabilities because of its all-water and day/night acquisition. In this paper, in order to contribute to a better evaluation of the potential of Sentinel-1 SAR imagery to track floods, we analyzed a multi-pulse flood caused by a typhoon in the Camarines Sur P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Floods in boreal forests were mapped by Voormansik, et al, (2014), who concluded that additional testing of the X-band sensor should be carried out with more detailed information regarding tree species, stand age, height and density. ESA's Sentinel-1 satellite pair offers a valuable SAR data source suitable for monitoring flood conditions (Twele, et al, 2016;Clement, et al, 2018;Ruzza, et al, 2019;Tsyganskaya, et al, 2019;Uddin, et al, 2019), especially in northern latitudes due to nearly daily temporal resolution. However, the land areas are regularly imaged only with VV-and VH-polarizations, which are less useful for detecting floods under forest canopy compared to HH-polarization (see section 2.2)…”
Section: Forest Floodsmentioning
confidence: 99%
“…Floods in boreal forests were mapped by Voormansik, et al, (2014), who concluded that additional testing of the X-band sensor should be carried out with more detailed information regarding tree species, stand age, height and density. ESA's Sentinel-1 satellite pair offers a valuable SAR data source suitable for monitoring flood conditions (Twele, et al, 2016;Clement, et al, 2018;Ruzza, et al, 2019;Tsyganskaya, et al, 2019;Uddin, et al, 2019), especially in northern latitudes due to nearly daily temporal resolution. However, the land areas are regularly imaged only with VV-and VH-polarizations, which are less useful for detecting floods under forest canopy compared to HH-polarization (see section 2.2)…”
Section: Forest Floodsmentioning
confidence: 99%
“…Based on the backscattering intensity of the SAR image where water appears as a dark area resulting in a low backscatter recording as incident radar signals are reflected away from the radar antenna (Henderson & Lewis, 1998), one can visualize and interpret flooding based on various classification methods. This includes a simple visual interpretation approach (Matgen et al, 2007;Oberstadler et al, 1997;Sanyal & Lu, 2004), image change detection (Bazi et al, 2005;Clement et al, 2018;Nico et al, 2000), region growing algorithms (Malnes et al, 2002;Mason et al, 2012), supervised classification (Pulvirenti et al, 2013;Townsend, 2002), histogram thresholding (Chini et al, 2012;Elkhrachy et al, 2021;Pulvirenti et al, 2016), and clustering algorithm (Ruzza et al, 2019). Further, many flood detection approaches have used a combination of thresholding, region growing, and change detection utilizing a single SAR image Matgen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing amount of satellite sensors providing freely available and continuous observations have encouraged investigations assessing their suitability for flood monitoring (Notti, et al, 2018;DeVries, et al, 2017;Twele, et al, 2016;Tsyganskaya, et al, 2019;Ruzza, et al, 2019;Reksten, et al, 2019;Kordelas, et al, 2018;Clement, et al, 2018;Uddin, et al, 2019;Du, et al, 2016). Considering spatial and temporal resolution, Sentinel-1 and Sentinel-2 have the potential to significantly improve flood monitoring capabilities.…”
Section: Discussionmentioning
confidence: 99%